Estimation of Aquifer Transmissivity Using Dar Zarrouk Parameters Derived from Resistivity Soundings on the Floodplain of River Dadin Kowa, Gombe State, Northeastern Nigeria - B. Ankidawa (Pouyan Press, 2018)
The shallow alluvial aquifers on the floodplain are the major sources of water supply for the dry season farming activities. The research is aimed to estimate the aquifer transmissivity of the alluvial formations on the floodplain using Dar Zarrouk Parameters derived from geoelectric soundings. Ten profiles of vertical electric soundings (VES) using schlumberger array method with the aid of a sensitive ABEM Signal Averaging System (SAS) was in the investigation. The results revealed five geoelectric layers on the alluvial formation of the floodplain. There were three, four, five, six and seven layers beneath the alluvial formation. The results were compared with the alluvial floodplain lithologies at each sounding points with resistivity values ranging between 0.98 Ωm to 4,113 Ωm and depths varying from 0.01 to 146 m. The geoelectric sequence of the alluvial formations of the flood plain reveals semi aquifer system. The aquifer hydraulic characteristics indicated that the transverse resistance R ranged between 436.8 Ωm2 to 77,324.40 Ωm2 with a mean value of 11,963.71 Ωm2. The longitudinal conductance S ranged between 0.0026 to 1.792 with an average value of 0.26348. The hydraulic conductivity value across the floodplain ranged between 0.16 m/day to 29.79 m/day with a mean value of 5.597 m/day. The transmissivity values obtained for the various layers range between 1.6 m2/day to 834.1 m2/day with an average value of 128.86 m2/day. The results of the hydraulic head reveal that the floodplain recharges the River. High groundwater potential zone occurs in the southern part of the study area